Discussing randomised clinical trials of cancer therapy: evaluation of a Cancer Research UK training programme. Issue 7488 (10th February 2005) - Jenkins, V; Fallowfield, L; Solis-Trapala, I; Langridge, C; Farewell, V
Abstract: Objective To evaluate a training intervention aimed at improving healthcare professionals' communication with cancer patients about randomised clinical trials. Design Before and after evaluation of training programme. Setting Members of the National Cancer Research Network, Scottish Trials Network, and the Welsh Cancer Trials Network Participants 101 healthcare professionals (33 clinicians and 68 research nurses). Intervention Four modules delivered by a trained facilitator using videotapes and interactive exercises to cover general issues about discussing randomised clinical trials with patients, problems specific to adjuvant trials, trials with palliation as the goal, and trials where patients had a strong preference for one treatment arm. Main outcome measures Before and after the intervention, participants were videotaped discussing a trial with an actor portraying a patient. These consultations were assessed for presence of information required by good clinical practice guidelines. The actor patients gave an assessment after each interview. Participants reported their self confidence about key aspects of trial discussion. Results Analysis of the videotaped consultations showed that, after intervention, significantly more participants displayed key communication behaviours such as explaining randomisation (69 v 81, odds ratio 2.33, P = 0.033), checking patients' understanding (11 v 31, odds ratio 3.22, P = 0.002), and discussing standard treatment (73 v 88, odds ratio 4.75, P = 0.005) and side effects (69 v 85, odds ratio 3.29, P = 0.006). Participants' self confidence increased significantly (P < 0.001) across all areas. Actor patients' ratings of participants' communication showed significant improvements for 12/15 key items. Conclusion This intensive 8 hour intervention significantly improved participants' confidence and competence when communicating about randomised clinical trials.